2007
DOI: 10.1071/rd06131
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor receptor types 1, 2 and 3 in placenta from pregnancies complicated by hypertensive disorders

Abstract: Abstract. The aim of the present study was to determine the expression of vascular endothelial growth factor (VEGF) family receptors (VEGFR) in placentas from pregnancies complicated by hypertensive disorders of different clinical severity. Placental tissue from women with gestational hypertension, pre-eclampsia, pre-eclampsia with haemolysis, elevated liver enzymes and low platelets (HELLP syndrome) and normotensive women, as a control group, was examined. Immunohistochemical techniques, reverse transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…In tumorigenesis, DC contribute to neovascularization via secretion of angiogenic factors 30,31 . Increased sVEGFR‐1&‐2 secretion has been shown for placental tissues from pregnancies complicated by hypertensive disorders 32 . Decidual DC display a distinct state of activation and our data support evidence that alternatively activated DC play a role within angiogenetic networks that are altered in insufficient placentation 33 .…”
Section: Discussionsupporting
confidence: 76%
“…In tumorigenesis, DC contribute to neovascularization via secretion of angiogenic factors 30,31 . Increased sVEGFR‐1&‐2 secretion has been shown for placental tissues from pregnancies complicated by hypertensive disorders 32 . Decidual DC display a distinct state of activation and our data support evidence that alternatively activated DC play a role within angiogenetic networks that are altered in insufficient placentation 33 .…”
Section: Discussionsupporting
confidence: 76%
“…The present study showed that, KDR expression was statistically significantly higher in control group as compared to either of the two PE groups (p<0.0005) and there is no statistically significantly difference between sPE and mPE (Table 2). Our studywas consistent with numerous studies which indicated that the KDR expression is low in pregnancies comlicated by PE than control [16][17][18][19]24].Other studies, have detailed additional levels of maternal plasma from sKDR during PE or early pregnancy while reducing intrauterine growth [20][21][22].…”
Section: Resultssupporting
confidence: 93%
“…Helske et al found that VEGFR2 was expressed almost exclusively in the endothelial cells of fetal placental vasculature and there was no difference in staining intensity between normal and preeclamptic samples [20] . However, Marini et al found lower protein levels of VEGFR-2 in placental vasculature in both preeclampsia and HELLP compared with controls [21] . Other reports describe a clear trophoblast localization of VEGFR-2, including cytotrophoblasts, the proximal column, endovascular cytotrophoblasts [10] and in all populations of extravillous trophoblasts in placental beds during normal pregnancy [22] .…”
Section: Discussionmentioning
confidence: 95%